KOMODIFIKASI SASTRA CYBER WATTPAD PADA PENERBIT INDIE - Arif Budi Mawardi (Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
Wattpad is the site that gives possibility to the internet users to read or share literary works of short story, novel, and poetry. Wattpad was launched in 2006 by Allen Lau and Ivan Yuen. Nowdays, it is considered as an electronic literature with significant development. Most of the users of Wattpad are from USA; and then followed by the Great Britain and Canada. It comes to Asia then gets into Indonesia. In Indonesia, there are so many very popular electronic literary writers on Wattpad and they are not satisfied with their works which are only shared on cyber world. They decide to publish their works through publisher. Commodification of electronic literary work to the printed one becomes interesting study in literature, the most important thing is on the production process. This study explains (1) The existence of the electronic literary writers on Wattpad, and (2) The commodification of Wattpad electronic literature to printed literature through the indie publisher.